2019
DOI: 10.4103/joacp.joacp_144_18
|View full text |Cite
|
Sign up to set email alerts
|

Single-point versus double-point injection technique of ultrasound-guided supraclavicular block: A randomized controlled study

Abstract: Background and Aims:This study aims to compare the single-point injection and double-point injection technique of ultrasound-guided supraclavicular block with regard to the success rate, time taken to perform the procedure, onset and duration of sensory and motor block, and complications.Material and Methods:A total of 60 American Society of Anesthesiologists physical status I and II patients between 20 and 50 years of age, with body mass index ≤30 kg/m2 posted for forearm surgeries, with anticipated surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…Advantages of musculoskeletal US include high resolution for the peripheral nerve, tendon, and muscle, high sensitivity for blood flow, and real‐time imaging of the needle tip and injection target, among others. More and more musculoskeletal procedures have been performed with US guidance, including joint injection, tendon sheath injection, bursa injection, and periperipheral nerve injection 9–12 . As for cervical transforaminal injection, most of the injections have been performed with fluoroscopy or CT guidance, whereas only a few studies have been found that uses US for guidance 13 .…”
mentioning
confidence: 99%
“…Advantages of musculoskeletal US include high resolution for the peripheral nerve, tendon, and muscle, high sensitivity for blood flow, and real‐time imaging of the needle tip and injection target, among others. More and more musculoskeletal procedures have been performed with US guidance, including joint injection, tendon sheath injection, bursa injection, and periperipheral nerve injection 9–12 . As for cervical transforaminal injection, most of the injections have been performed with fluoroscopy or CT guidance, whereas only a few studies have been found that uses US for guidance 13 .…”
mentioning
confidence: 99%
“…A total of 53 articles were included in this systematic review: 38 hand studies and 15 shoulder studies ( Table S1 , available on the Journal’ s website at www.jhsgo.org ). 18 , 19 , 20 , 21 , 23 , 24 , 25 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 These 53 articles comprised 73 discrete, surgery-block combination study groups (54 hand and 19 shoulder groups) and 6,579 total subjects (2,875 hand and 3,704 shoulder subjects; Table 1 ). The large majority of studies in both groups were RCTs (94.4% hand and 78.9% shoulder RCTs); most were single-blind.…”
Section: Resultsmentioning
confidence: 99%
“…However, the optimal needling technique for the SB is remaining controversial. Various studies have proposed a series of techniques of where to first inject the LA and how many injections to perform around the brachial plexus, which include single-, double-, triple-, targeted intracluster-, or modified-injection techniques for the last nearly two decades [ 3 6 , 9 , 11 , 16 ]. Up to now, the most common techniques for LA injection described at the first rib level are a single or double injection.…”
Section: Discussionmentioning
confidence: 99%